PENGARUH PENGALAMAN AUDITOR, LOCUS OF CONTROL, DAN PENGETAHUAN MENDETEKSI KEKELIRUAN PADA AUDIT JUDGMENT - Christanti, Made Puspita; Dwirandra, A.A.N.B (E-Jurnal Akuntansi; Vol 18 No 1 (2017), 2017)
This research was conducted on a public accounting firm in Bali with the primary data collection method is using questionnaire data. The number of samples analyzed were 42 respondents using purposive sampling method of sampling. Data have valid and reliable, meet the classic assumption test, analysis technique used is Multiple Linear Regression Analysis with software SPSS.Hasil end of the study states that the auditor's experience, locus of control and knowledge to detect mistakes positive effect on audit judgment. Thus, it can be concluded to obtain an accurate audit judgment required considerable experience in auditing financial statements and have an internal locus of control is good so that the auditor believes has kekampuan face challenges and threats while performing the task. Knowledge is also important when auditors perform assignments particular knowledge in detecting errors to get the final result is accurate in making audit judgments.
Keywords: experience, locus of control, knowledge detect errors, audit judgment